The rhetoric of martyrdom in the Jesuit relations of New France, 1632-1650 - Knox, M (2015)
This thesis identifies in the Relations des Jésuites de la Nouvelle-France (Relations), written between 1632 and 1650, a comprehensive rhetoric of total selfoffering to Jesus Christ, a rhetoric of martyrdom, rooted in their authors' particular experience of the Christian tradition, their praying with the Spiritual Exercises (1548) of Ignatius Loyola (1491-1556), their encounters with the spirituality of the French Jesuit Louis Lallemant (1578-1635), and their exposure to various forms of Jesuit mission literature from around the world. Published annually, these Relations were the only consistent account of the unfolding French colonial project in Nouvelle- France, and a popular read among the noblesse, ecclesiastics, and pious Christians of the kingdom. Today they form an essential collection of primary sources that continue to provide a doorway into the earliest days of Canada's history. Identifying this rhetoric throughout the narratives, this study endeavours to provide a deeper historical understanding of these Relations by contextualising their content within the particular all-encompassing religious worldview of the authors who wrote them. The religious imaginations of these Jesuit authors, Paul Le Jeune (1591-1664), Jean de Brébeuf (1593-1649), Françoise-Joseph Le Mercier (1604-90), Barthélemy Vimont (1594-1667), Jérôme Lalemant (1593-1673), Isaac Jogues (1607-1673) and Paul Ragueneau (1608-1680), thus gives birth to a rhetoric in the Relations that presents Nouvelle-France as a land filled with Amerindian peoples who would only truly embrace Christianity if all of the missionaries lovingly offer their lives to Jesus Christ; just as He had done for the salvation of the entire world from sin and evil. They do so by placing their efforts on a metaphysical plane. There, the missionaries are presented as having been invited by God to join Christ crucified on a mission into a land filled with suffering and death. Where the Amerindians they evangelise must choose between a barbarous life of selfish material interest that is thought to imbue their traditions and a more human life of self-offering modelled on the Christian God. At the same time Satan, the devil, labours hard not to lose his grip on a part of the world that was as yet unaware of its true divine origins. The 'divine', the 'missionary', 'Satan', and the 'Amerindians', locked in this cosmic battle for souls that can only be won through a self-sacrificing union with Jesus Christ, combine to form the rhetoric of martyrdom in the narratives that reaches its summit as the authors describe the murders of eight of their fallen comrades, tortured and killed by some of the very people they had come to evangelise. This rhetoric, present throughout the narratives, has yet to be acknowledged, analysed, and interpreted by historians. In doing so, it is hoped that this study will deepen any reading of the Relations, advancing our understanding of their full import for both the early modern and the present-day reader.